2002
DOI: 10.1017/s1041610202008256
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Training Dementia Caregivers in Sensitivity to Nonverbal Emotion Signals

Abstract: Ninety-one mid- to late-stage dementia patients residing in nursing homes, along with their staff caregivers, participated in a study designed to assess whether training caregivers in sensitivity to nonverbal communication could enhance mood and reduce symptoms in patients and improve psychological well-being in caregivers. Patients and staff at three nursing homes comprised three groups that were randomly assigned to either a non-verbal sensitivity group, a behavioral placebo group that received instruction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(130 citation statements)
references
References 31 publications
(26 reference statements)
3
121
0
6
Order By: Relevance
“…Accordingly, there is considerable agreement in the literature on the need for specialized training for geriatric health care staff [1,[11][12][13][14][15][16]. The communication problems of staff members can be summarized as negative stereotypes about residents and their communication needs, undervaluing communication compared to physical and medical aspects of patient care and restricted communication style [1].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there is considerable agreement in the literature on the need for specialized training for geriatric health care staff [1,[11][12][13][14][15][16]. The communication problems of staff members can be summarized as negative stereotypes about residents and their communication needs, undervaluing communication compared to physical and medical aspects of patient care and restricted communication style [1].…”
Section: Introductionmentioning
confidence: 99%
“…Key studies on valuing care workers Kihlgren 1990Kihlgren , 1996Williams 1994;Hagen 1995;Matteson 1997;Moniz-Cook 1998;McCallion 1999;Proctor 1999;Wilkinson 1999;Lintern 2000;Wells 2000;Magai 2002;Testad 2005;Davison 2007.…”
Section: Box 1 Three Stages Of Educationmentioning
confidence: 99%
“…Key studies on care plans Kihlgren 1990Kihlgren , 1996Ripich 1995;Palmer 1996;Matteson 1997;Middleton 1999;Proctor 1999;Lintern 2000;Wells 2000;Burgio 2001Magai 2002;Roth 2002.…”
Section: Care Plansmentioning
confidence: 99%
“…Improvement was associated with lower social anxiety and higher self-worth in girls but not in boys (Grinspan, Hemphill, & Nowicki, 2003). Another study realised with a nursing staff caring for demented persons has shown that training to recognise nonverbal signals enhanced staff's satisfaction, diminishing negative affect without having an impact on demented persons' symptomatology (Magai, Cohen, & Gomberg, 2002). A computer programme has been developed in order to increase the ability to read EFE by Asperger and Autistic children.…”
Section: Possibility To Treat Efe Decoding Dysfunctionsmentioning
confidence: 99%